2018
DOI: 10.5032/jae.2018.02143
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Framework for School Garden Program Development and Evaluation: A Delphi Approach

Abstract: School gardens programs and garden-based education are positioned to become fixtures in educational institutions given recent trends and the national interest in gardens at school sites. Agricultural education professionals have integrated school gardens into core science, social studies, math, and language arts courses as well as agricultural education programs for elementary, middle, and high school curriculum. The literature shows that while there are specific curriculum links being made, school garden prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…A modified Delphi technique was selected as the best research method to address the objective of this study. Delphi approaches have been used previously to establish programmatic objectives (Diaz et al, 2018;Long & Morgan, 2010), to revise educational curriculum (Lundy et al, 2017), and to identify essential professional competencies needed in agricultural settings (Edgar et al, 2012;Conner et al, 2013;Ramsey & Edwards, 2011;Sapp et al, 2019). Stewart (2001) suggested that a modified Delphi can be used to gather a consensus of knowledge from experts when distant communication is convenient over traditional face-to-face settings.…”
Section: Methodsmentioning
confidence: 99%
“…A modified Delphi technique was selected as the best research method to address the objective of this study. Delphi approaches have been used previously to establish programmatic objectives (Diaz et al, 2018;Long & Morgan, 2010), to revise educational curriculum (Lundy et al, 2017), and to identify essential professional competencies needed in agricultural settings (Edgar et al, 2012;Conner et al, 2013;Ramsey & Edwards, 2011;Sapp et al, 2019). Stewart (2001) suggested that a modified Delphi can be used to gather a consensus of knowledge from experts when distant communication is convenient over traditional face-to-face settings.…”
Section: Methodsmentioning
confidence: 99%
“…How does the absence of a structured mentoring program impact a first-year agricultural education teacher? Responses were narrowed to unique statements and grouped into like themes (Diaz et al, 2018). Responses from 25 panel members were collected in this round for a response rate of 59.52%.…”
Section: Methodsmentioning
confidence: 99%
“…The number of iterations is dependent on the level of consensus that is desired (Hsu & Sandford, 2007). Advisory panel design (Diaz, Warner, & Webb, 2018) was used to review the initial questionnaire statements for content validity. A review panel of four participants was convened to evaluate and revise the instrument for content validity purposes.…”
Section: Methodsmentioning
confidence: 99%